Feasibility Analysis of QR Code-Based Ready-to-Wear Fashion as a Creative Innovation in the Fashion Industry - Ismi Nur Aini Azizah; Wulansari Prasetyaningtyas (Universitas Negeri Semarang, 2026)
This study aims to describe the process of making QR Code-based ready-to-wear clothing, analyze the feasibility of fashion based on six indicators, and explain the role of QR Code as an informative fashion identity. The research approach uses a quantitative descriptive method with a survey design. The object of the research consisted of a set of ready-to-wear clothing, including sleeveless batik underwear, a crop blazer with a strappy collar featuring an embroidered QR Code on the back, and cargo pants. Feasibility data were obtained through an assessment instrument containing thirty statements that included indicators of design, size, aesthetics, sewing techniques, fashion performance, and specialties. These statements were assessed by expert panelists and trained panelists, who evaluated them based on their knowledge and experience in the fashion field. The data was analyzed using percentage descriptive techniques to determine the category of fashion feasibility in each indicator and as a whole. The study's results showed that QR Code-based ready-to-wear clothing achieved an average feasibility level of 93.08%, categorized as very feasible, with assessments of 92.53% from expert panelists and 93.63% from trained panelists. All indicators fell within the very feasible category. The embroidered QR Code on the back of the blazer acts as a visual accent that is in line with the theme of Teknika and serves as a link to digital information about the concept and philosophy of the work, thereby strengthening the fashion identity while showing the potential use of digital technology as an information medium in fashion products.